Does the AO/OTA fracture classification dictate the anesthesia modality for the surgical management of unstable distal radius fractures? A retrospective cohort study in 127 patients managed by general vs. regional anesthesia - Sascha Halvachizadeh; Merav Dreifuss; Thomas Rauer; Anne Kaiser; Dirk Ubmann; Hans-Christoph Pape; Florin Allemann (Patient Safety in Surgery)
Abstract Introduction Regional anesthesia increases in popularity in orthopaedic surgery. It is usually applied in elective surgeries of the extremities. The aim of this study was to assess indication of the use of general anesthesia in the surgical treatment of distal radius fractures. Methods Patients undergoing surgical fixation for distal radius fractures between January 1st, 2020, and December 31st, 2021, were included. Exclusion criteria encompassed incomplete 12-month follow-up, transferred or multiply injured patients, those with prior upper limb fractures, or admission for revision surgeries. Patients were categorized by anesthesia type: GA or plexus block anesthesia (PA). Primary outcomes comprised tourniquet utilization and duration of surgery, while secondary outcomes encompassed complications (e.g., complex regional pain syndrome [CRPS], local wound infection, implant removal necessity) and range of motion at three, six, and twelve months post-surgery. Fractures were classified using the AO/OTA system. Results The study enrolled 127 patients, with 90 (70.9%) in Group GA and 37 (29.1%) in Group PA. Mean patient age was 56.95 (± 18.59) years, with comparable demographics and fracture distribution between groups. Group GA exhibited higher tourniquet usage (96.7% vs. 83.8%, p = 0.029) and longer surgery durations (85.17 ± 37.8 min vs. 65.0 ± 23.0 min, p = 0.013). Complication rates were comparable, Group GA 12.2% versus Group PA 5.4% p = 0.407, OR 2.44; 95%CI 0.51 to 11.58, p = 0.343). Short-term functional outcomes favored Group PA at three months (e.g., Pronation: 81.1° ± 13.6 vs. 74.3° ± 17.5, p = 0.046). Conclusion Solely classifying distal radius fractures does not dictate anesthesia choice. Complexity of injury, anticipated surgery duration, less use of tourniquet, and rehabilitation duration may guide regional anesthesia utilization over GA in distal radius fracture fixation.